PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN PARTISIPATIF DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DIRA SHOPPING CENTRE BALUNG JEMBER - Fuad Zulfikar Isman; Sudarsih Sudarsih; Susanti Prasetiyaningtiyas; Supriyadi Supriyadi; Nurhayati Nurhayati (Study Program of Management Faculty of Economics and Business University of Jember, 2023)
In order to strengthen the manpower of a company, the company itself needs to manage its employees in such a way as to develop professionalism and be able to achieve the expected quality of employee performance. Work performance is the result of qualitative and or quantitative work carried out by employees in accordance with their responsibilities. Creating a decent work performance helps the company to achieve its goal. Several things that can be done involve creating organizational culture that suits the employees' condition, applying participative leadership towards employees and work discipline which conforms the rules. This research has independents variables, includes organizational culture, participative leadership, and work discipline. Meanwhile the dependent variable is work performance. The goal of this research is to examine and analyze the influence of organizational culture, participative leadership and work discipline towards work performance of the employee of DIRA Shopping Centre Balung Jember. Population of this research are 150 employees and the sampling method is cluster random sampling. It is used when the population seems to be wide and there are groups which look the same, but are actually different internally. There are 110 employees that are taken as sample of this research. The data analysis method that is used is multiple linear regression. The result of this research shows that organizational culture, participative leadership and work discipline significantly influences the work performance of the employees of DIRA Shopping Centre Balung Jember.